Band structure analysis of (1×2)-H/Pd(110)-pr - Shuttleworth, I.G. (Surface science, 2013)
A novel method of band structure analysis based on the atomic orbital (AO) coefficients in LCAO-DFT has been applied to the (1×2)-H/Pd(110)-pr system. The analysis has revealed symmetry-dependent Pd 4d band splitting due to H ligand effects; ensemble effects due to the (1×2) Pd reconstruction are shown to be relatively minor. [Display omitted] •A novel analysis method of projecting LCAO-DFT coefficients into the electronic band structure is presented.•Coefficient band structure analysis identifies regions of high and low H-Pd resonance in k-space.•Dominance of ligand over ensemble effects in the (1×2)-H/Pd(110)-pr is demonstrated.